(untitled) (International Journal of Irrigation and Water Management, 2018)
Subsurface drip irrigation (SDI) is a most advanced method of irrigation that facilitates the irrigation of crop / plants with small amounts of water through the T- tapes placed below the soil surface. Depth of T-tape and requirement of water depends upon soil type and crop under observations. Experiments for comparative study of SDI with flood irrigation for yield and quality were conducted on sugarcane crop from 2005 - 2008 with 3-varieties i.e. HSF-240, HS- 12 and CSSG-668 on an area of 6 ha. Drip tapes were buried manually in the middle of the ridges on an area of 3 ha with subplot size for each variety of 1 ha compared with flood irrigated crop of 3 ha with subplot of 1 ha for each variety. Flood irrigation system showed better results for growth, yield and quality of sugarcane than SDI. Germination % and tillers/plant did not show any significant difference under both irrigation systems. SDI resulted to lower mill- able cane, cane yield, crop growth rate (CGR) and net assimilation rate (NAR). Harvest index % (HI) had no significant effect on both irrigation systems. Higher leaf relative water contents (LRWC) obtained under flood irrigation showed higher accumulation of water supplied through flood system. Similarly, quality attributes (juice extraction, purity %, recovery % cane and sugar yield t/ha) showed superior behavior under flood irrigation than SDI. Flood irrigation system provided net benefits ranging from Rs. 56130 – Rs. 82760 / ha while SDI resulted in loss from Rs. 127345 to 157910 / ha. Maximum income benefit was recorded in CSSG-668 variety (Rs. 82760 / ha) and maximum loss in HSF-240 variety (Rs. 157910 / ha) under SDI. SDI helped to save water from 11 - 18% over flood irrigation system that had no significant contribution in net benefits. This loss may be due to the major problems faced by SDI system that led to blockage, damaged of T tapes, filtration obstructions due to high ferrous contents in irrigated water, higher initial cost, management, that resulted to net economic loss in sugarcane. Irrigated water was unfit with high ferrous contents that resulted to blockage of T -tapes. SDI saved 18% water as compared to flood irrigation system. It was concluded that SDI is not a superior system of irrigation for sugarcane in developing countries like Pakistan where water is unfit for irrigation. Its high installation cost, breakage and clogging resulted to net economic loss. SDI might be a superior system where water is fit for irrigation, free of ferrous and low installation costs.